APPLICABILITY OF FORESTRY TO INFERTILE UPLANDS OF NORTHEAST THAILAND - Chuntanaparb, Lert; Wacharakitti, Sathit; Hoamuangkeaw, Wuthipol (วารสารวนศาสตร์ไทย, 2024)
This article encompassed the essences of research results of The Land Use Project, The Pilot Village Woodlot Project, and The Rainfed Farming System Project in the northeast. The subject elaborated the northeast population including economical condition, constrains in its physical factors and status of forestry practice. Suggestions, from research experiences, were also given the practical means of integrating forestry in to upland farming system of the northeast.